Electric machines : theory, operating applications, and controls - Hubert, Charles I. (New Delhi Pearson, 2002)
Retaining the user-friendly style of the First Edition, the Second Edition of this unique book provides detailed information on the application and safe operation of motors, generators, and transformers at the Technology Level, and includes examples in the use of NEMA and NEC Standards. With an emphasis on current industrial standards, this book presents AC machines and transformers before DC machines, motors before generators, gives more attention to machine characteristics, and makes extensive use of NEMA standards and tables. For Applications Engineers, Electrical Engineers, Maintenance Engineers, Marine Engineers, Mechanical Engineers, Nuclear Engineers, Operating Engineers, and Petroleum Engineers, who want an easy-to-understand, yet detailed explanation of the current industrial standards in the field of Electronics.